The Ability of Adults of Different Size to Egress Through Confined Space Apertures. (September 2019) - Stewart, Arthur; Nevill, Alan; Johnson, Christopher
Objective: To determine minimum egress apertures in healthy adults of different body size. Background: Body space requirements have traditionally been considered from an industrial perspective, facilitating safe confined-space working. However, increased typical body size resulting from global obesity renders traditional assumptions of body size inappropriate. This has potentially far-reaching consequences for evacuation planning, due to diminished clearance space, slower movement, and increased chance of physical entrapment. Critically, no current literature describes the minimum apertures adults can negotiate. Method: Forty-eight men and 40 women underwent anthropometric and 3-D scanning assessments from which anatomical dimensions were extracted. Additionally, a wall egress task was undertaken through an aperture that was progressively narrowed until individuals failed to pass. Minimum egress aperture was predicted from anatomical variables using backwards elimination regression. Results: Minimum wall egress was best predicted from mass, abdominal depth, bideltoid breadth and chest depth. Passes and fails, discriminated using binary logistic regression, identified chest depth and abdominal depth as influential for wall egress success at selected apertures, with a gender interaction manifest at abdominal depth. Conclusion: Minimum egress aperture relates to body size and can be predicted from anatomical variables; however, men and women display subtle differences in egress capability. Application: In public and industrial settings, egress capability in restricted spaces is affected by size and gender, with profound implications for safety, which relate to increased typical body size associated with global obesity.